A Monte Carlo Investigation of Characteristics of Optimal Geometric Mean Portfolios - Maier, Steven F.; Peterson, David W.; Weide, James H. Vander (Journal of Financial and Quantitative Analysis, 1977)
Steven F. Maier, David W. Peterson, James H. Vander Weide, A Monte Carlo Investigation of Characteristics of Optimal Geometric Mean Portfolios, The Journal of Financial and Quantitative Analysis, Vol. 12, No. 2 (Jun., 1977), pp. 215-233